Metode Dakwah Bil Haal Ustadzah Zainiyah Menumbuhkan Karakter Disiplin Siswa Ma'hadul Qur'an Putri Ponpes Salafiyah Syafi'iyah Sukorejo Situbondo - Aminul ‘Alimin (Jurnal Multidisiplin Ibrahimy, 2024)
Da'wah methods are certain methods that can be used by Ustadzah Zainiyah as an educator and preacher to convey Islamic law to mad'u (for example students as his students). The problem formulation of this research is how to apply Ustadzah Zainiyah's bil haal da'wah method in an effort to foster the disciplined character of Ma'hadul Qur'an students at the Salafiyah Syafi'iyah Islamic Boarding School in Sukorejo, Situbondo? Meanwhile, the aim to be achieved is to determine the process of implementing Ustadzah Zainiyah's bil haal da'wah method in an effort to foster the disciplined character of Ma'hadul Qur'an students at the Salafiyah Syafi'iyah Islamic Boarding School in Sukorejo, Situbondo. This research is a type of qualitative research with descriptive methods. Data collection techniques using observation, interviews and documentation. To check the validity of the data, researchers used source triangulation. After this research process, the research results were obtained, that Ustadzah Zainiyah's bil haal da'wah method that was applied was trying to set an example in various things. The examples referred to here include, upholding STW (prayers on time), never a day without doing charity, not a day without reading the Koran, muraja'ah memorizing the Qur’an every day, dressing clean, holy, neat and fragrant.